Indústria, conjuntos habitacionais e assentamentos precários : o distrito de Carapina, município da Serra (ES) de 1966 a 1995 - Fiorotti, Alexandre (2014)
Discusses the large industries, port, planning and law importance, in their different interfaces with Carapina’s, district in the municipality of Serra, Espírito Santo State, setup process and territorial reconfiguration. Starting from the assumption that